2019
DOI: 10.31349/revmexfis.65.159
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear structure study of [22,24]Ne and [24]Mg nuclei

Abstract: Shell model calculations based on large basis has been conducted to study the nuclear structure of $^{20}Ne$, $^{22}Ne$ and $^{24}Mg$ nuclei. The energy levels, inelastic electron scattering form factors and transition probabilities are discussed by considering the contribution of  configurations with high-energy beyond the model space of sd-shell model space which is denoted as the core polarization (CP) effects.~The Core polarization is considered by taking the excitations of nucleus from the $1s$ and $1p$ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The effective proton and neutron charges used in these calculations are 0.5 and 1.0, respectively. Figures 10,11,12. show the CDD obtained with the investigated Skyrme parameterization Sk35-Skzs*used in this work as well as the experimental charge distributions for 64,66,68 Zn isotope. The comparison of the predicted theoretical values was compared with the available measured data for CDD and C2 form factors and showed good agreement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effective proton and neutron charges used in these calculations are 0.5 and 1.0, respectively. Figures 10,11,12. show the CDD obtained with the investigated Skyrme parameterization Sk35-Skzs*used in this work as well as the experimental charge distributions for 64,66,68 Zn isotope. The comparison of the predicted theoretical values was compared with the available measured data for CDD and C2 form factors and showed good agreement.…”
Section: Resultsmentioning
confidence: 99%
“…In model space calculations, Radhi et al [6][7][8][9] showed that it is advisable to include CP effect in form-factors for nuclei in the beginning of p-shell and the end of sd-shell. F. A. Majeed et al [10][11][12] demonstrated that form factor calculations based on large-basis of the shell model to study the nuclei in the p, sd and fp shells considering the contribution of high-energy configurations beyond the p, sd and fp shell space model space denoted as the core polarization effects. The proton and neutron matter density distribution and their related charge radii along with the ground state form factors have been investigated by Hameed BS 13 for some selected potassium isotopes, their conducted study showed that taking into consideration the core polarization effects along with effective g-factors made remarkable enhancement in their calculations which leads to good agreement with the measured data.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Navratil et al [10] it is found that the predicted rate of the E2 transition with 4ℏ𝜔 space for 6 Li is weaker than 6ℏ𝜔 space prediction. Majeed et al [11][12][13] revealing that the form factor calculation on a large basis of the shell model was used to analyze nuclei in the p, sd, and Fp shells, including the contribution of high-energy configurations beyond the p, sd, and Fp shell space model space is essential to be considered to consider the effect of the core polarization contribution arises from the closed core.…”
Section: Introductionmentioning
confidence: 99%
“…The melting of the N = 20 shell for neutron-rich systems using the interaction tensor part contribution in SHF theory was investigated by Bhattacharya [14] for the nuclei 40,48 Ca and 56 Ni, as well as the new magic numbers are introduced at N = 16, 32. The core polarization effect is considered by using a microscopic theory that allows the excitation from the core nucleons and projects them to the model space with exciton energy 2 and 4 ω were conducted by Majeed and his collaborators, for some p, sd, and f p nuclei, show great success in describing the form factors compared to the observed data [15,16,17,18]. Shaimaa A. Abbas et al conducted a study to investigate the form factors and the related distribution of the charge density for the inelastic Coulomb C2 for 58,60,62 Ni and 64,66,68 Zn isotopes by utilizing the method of SHF with the parametrization of type (Sk35-Skzs * ).…”
Section: Introductionmentioning
confidence: 99%